Effect of adhesive system and application strategy on reduction of dentin permeability - Adriana Oliveira Carvalho; Marcelo Tavares de Oliveira; Toru Nikaido; Junji Tagami; Marcelo Giannini (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This study evaluated the effect of adhesive systems and application strategies on dentin hydraulic conductance (HC). The buccal enamel was removed from bovine incisors to simulate laminate cavity preparations. After removing the roots and the coronal pulp, the buccal dentin was treated with EDTA solution (0.5 M) for 5 minutes, rinsed, ultrasonicated for 12 minutes and connected to a permeability device. HC of the specimens was measured at 10 psi (n = 5). Permeability was measured before and after bonding procedures using G-Bond (GB), Clearfil Tri-S Bond (CTS), Hybrid Coat (HY), Bond Force (BF), Adper Easy Bond (AEB) Silorane (SI), Clearfil SE Bond (CSE) and Adper Scotchbond Multi-Purpose (SMP) adhesives systems, which were applied following three strategies: 1) according to the manufacturers' instructions; 2) two coats of all-in-one self-etching adhesives (GB, CTS, HY, BF, AEB) or priming step plus two coats of bonding resin for the other systems (SI, CSE and SMP); and 3) a thin layer of a flowable composite applied over one coat of all-in-one self-etching adhesives or primed surface for SI, CSE and SMP adhesives. No significant difference was observed among the application modes concerning their ability to reduce HC. None of the adhesives showed complete sealing (100%) of the bovine tooth dentin. SI exhibited lower HC than SMP, however, they were not significantly different from the other systems. The results suggest that all systems tested result in an HC reduction of more than 90%. The wet bonding technique seemed to be more sensitive for dentin sealing.